2020
DOI: 10.1108/lm-01-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Increasing or decreasing reading trend: an overview of the current status of the public libraries in Khyber Pakhtunkhwa, Pakistan

Abstract: PurposeAs the human race moved from the Paleolithic to the current phases of the Neolithic period, the learning process developed from inscriptions on stones to clay tablets, from papyrus to papers and, ultimately, to digital technology. From ancient times to the present, public libraries have become open universities that are more democratic in the provision of educational and information services and the preservation of cultural heritage, regardless of gender and belief. This study attempts to understand rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Administrative competence in deploying technology introducing innovation boosts users’ satisfaction in using library services. In addition to academic activities, in difficult situations (such as COVID-19), vigilant leadership formulates emergency measures to continue to provide users with uninterrupted academic services (Rafi et al , 2020a). Thus, the influence of qualified leadership revealed a significant effect on productivity and satisfaction with library services in the fourth hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Administrative competence in deploying technology introducing innovation boosts users’ satisfaction in using library services. In addition to academic activities, in difficult situations (such as COVID-19), vigilant leadership formulates emergency measures to continue to provide users with uninterrupted academic services (Rafi et al , 2020a). Thus, the influence of qualified leadership revealed a significant effect on productivity and satisfaction with library services in the fourth hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan's Higher Education Commission, established in 2002, has facilitated access to a range of databases for all public and private universities and subsequently to public libraries where the use of database resources is limited for quality education and research (Rafi et al, 2019a(Rafi et al, , 2019b. However, compared to universities, the utilization rate of these databases is extremely low in public libraries due to lack of digital literacy, defective technologies and infrastructure that need major reforms (Rafi et al, 2020a). In addition, it has been found that the deployment and use of the latest technology in the academic environment is very slow, and universities far away from big cities require direct government involvement to fill the gaps in increasing technology, use resources and improve the overall academic activity (Rafi et al, 2020a(Rafi et al, , 2020b(Rafi et al, , 2020c(Rafi et al, , 2020d.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is further suggested in the study that librarians should keep themselves aware of the new published material as well as about the information resources that are still in pipe and their publication is expected in near future. (Rafi, Ahmad & Jian, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the above discussion, it can be concluded that a research gap can be assessed from an angle of a dearth of studies conducted on public libraries as well as on health-care libraries. This may be the reason behind the deteriorating status of public libraries especially in maintaining the service quality (Baada et al, 2019;Rafi et al, 2020;Sin and Kim, 2008;Singh, 2012). Library services.…”
Section: Emerging Patterns and Trends Reflected On Lsq Studiesmentioning
confidence: 99%